Carrying capacity and its implications in a Chinese ancient village: the case of Hongcun. Issue 3 (4th March 2018) - Zhao, Guiling; Deng, Zongji; Shen, Jun; Ryan, Chris; Gong, Jinhua
ABSTRACT: Hongcun, an ancient village in Anhui in China, is an UNESCO-gazetted village because of its Huizhou architecture. It attracts over 1.6 million visitors per annum. Based upon a simple spatial model, the results of this study indicate that its social carrying capacity is being vastly exceeded, and the consequences are discussed in terms of the impacts on village life using data derived from a survey of residents. In terms of addressing the issues of crowding, it is suggested that a number of future choices face the village, ranging from the imposition of quotas on visitation to sustain and protect its UNESCO status by significantly reducing overcrowding, or alternatively, to embrace mass tourism to become akin to a theme park that is based on Huizhou culture.